Factors that influences the effectiveness of training program in Syarikat Air Melaka Berhad (SAMB) / Kamaliadriwanti Mohd Faizal - Mohd Faizal, Kamaliadriwanti (Faculty of Business and Management, 2009)
This report investigates the factors that influence the effectiveness of training in Syarikat Air Melaka Berhad. This study wants to find out the factors which influence the effectiveness of training program provided by Syarikat Air Melaka Berhad to the employees. Training program is very important to the company because its will educate the employees to perform well in the job. Besides that, it will develop the career of the employees to make them better in the future. There is no research done by the manager in Department of Human Resource at Syarikat Air Melaka Berhad (SAMB) regarding to identify and examine the effectiveness of training program provided by the company. So, the organization needs to carry out the research to identify the factors that influence effectiveness of training program in order to achieve the organization objective. The purpose of conducting this study is to indicate the factors which influence the training program in providing the good performance among employee in Syarikat Air Melaka Berhad. A total of 50 respondent self-administered questionnaires were distributed and collected simultaneously which have resulted a 100% response rate. Using quantitative analysis, the data were computed by using SPSS program to convert the frequency into percentage. From the result obtained, improve productivity has a very strong significant compare others factors. From the finding we can conclude that the effectiveness of training program will give big impact toward the productivity of the employees. Researcher hopes that the results and recommendations can help Syarikat Air Melaka Berhad (SAMB) to provide the good training in the future to make the improvement in the performance of the employees in their works in order to achieve the goals and objective of the company.